MOSTRA ONLINE DE TEATRO NA ESCOLA: CRIANDO OUTROS TERRITÓRIOS PARA A PRÁTICA DA MEDIAÇÃO TEATRAL EM CONTEXTO MARANHENSE - PEREIRA, João Victor da Silva (2021)
The research entitled " Online Festival of Theater in School: creating other territories for the practice of theatrical mediation in the context of Maranhão ", of qualitative approach and interventional and descriptive nature, intended to trigger the methodology of action research when proposing an intervention of audience formation in performing arts in the state of Maranhão, in which three artistic- pedagogical instances are involved (teachers, students and artists), from the production of an online exhibition of theater in school. It is used to discuss the cultural mediation authors such as Wendell (2011a; 2011b), Martins (2008), Barbosa and Coutinho (2009); theatrical mediation directly related to the practice 'with the scene' in Pupo (2016), Wendell (2011), Casemajor; Lamoureux; and Racine (2006); the discussions about art as experience, pedagogy of the spectator, participatory art in the contemporary scene, use of virtual media in the scene and theater as a convivial and technovivial event, with the studies elaborated, mainly by Barbosa (2001), Desgranges (2008; 2010; 2011; 2017), Larrue (2020); and Dubatti (2007; 2020). The research adopted in its methodological path three stages: 1) bibliographic and documental research, to deepen the concepts and intend the practices of cultural mediation as public policy of the state of Maranhão; 2) research-action, foreseeing the stages of artistic residence; formative webinars with teachers of the area; and the production of the online exhibition of theater in the school with a program of theatrical mediation involving the instances of culture and education; 3) analysis and discussion of the production of the online exhibition of theater in the school from the presented bibliography. From the investigation, it raises reflections about the transformations and artistic and pedagogical contributions regarding the studies about theatrical mediation and analyzes the production of the school theater show as a propitious space for theater mediation in the state of Maranhão.